Evaporated mongo milk - Fernandez, Elizabeth M. (College of Engineering, 1976)
This plant which is designed to produce milk from mango beans will have a capacity of 47,000 metric tons a year or 118,000,000 of 14 oz. cans a year. It is to operate 24 hours a day for 300 days a year, requiring a fixed-capital investment of P 8,907,290. With a unit cost of P 0.75 per 14 oz. can of milk and an added income from animal feeds of P 0.78 per kilogram, total annual sales will amount to P 92,904,652. The pay-out time is 1.84 years making this plant economically feasible.